Pentingnya Manajemen Pemasaran bagi Pelaku UMKM di Kelurahan Wonorejo, Kecamatan Rungkut, Kota Surabaya - Orell Xalansa Ludbiyanto; Tri Kartika Pratiwi (Jurnal Masyarakat Mengabdi Nusantara, 2023)
Micro, small and medium enterprises (MSMEs) are one of the highest record holders in this type of sales in Indonesia, both in MSMEs engaged in online media or those that appear physically. In carrying out MSME activities, of course there is a lot that must be observed so that later they can be appropriate, namely with the strategy. Marketing strategy or sales technique is an important role in the business world, especially in today's business competition. Apart from showing the taste and attractive packaging, of course we have to analyze the market so that we can then determine the target and media to use. The importance of marketing management for MSME actors must be emphasized, such as a good marketing strategy, how to determine the target market to determine social media as a promotional tool.